Comparing The Argumentative Essay Formats of Indonesian and Korean Students Using the Toulmin Model - Yanuarius Yanu Dharmawan; Helena Verusha Ali; Bayu Andika Prasatyo; Amaliah Amaliah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study's overarching goal is to dissect and contrast the organizational framework of persuasive compositions generated by Indonesian and Korean (South Korean) pupils who are acquiring English as a secondary language, utilizing the Toulmin model as a theoretical framework for argument assessment. The research sample consisted of five participants from Indonesia, five participants from Korea, five female participants from Indonesia, and five female participants from Korea. Typically, individuals originate from diverse educational and vocational contexts. The articles generated by the authors served as the focal point of an analysis that employed elements of the Toulmin framework. The research's findings imply that there is no appreciable difference between men's and women's levels of reasoning in the two countries. It was evident that a discernible distinction among the participants was the absence of counterargument sections in certain individuals. This study holds significant importance in terms of examining the impact of cultural factors inherent in each nation and its language on the principles of argumentative writing. The results obtained from the investigation conducted in this research. can be employed to improve pedagogical strategies and facilitate the development of writing curricula that are culturally appropriate. It is anticipated that future investigations will facilitate the examination of additional linguistic and cultural attributes, as well as the broadening of the research's purview to encompass a more heterogeneous cohort hailing from a greater array of nations, as well as persons with differing levels of scholarly attainment.